Delineating the mode of action used by lithium in modulating oxidate stress and inflamation in activated macrophage cells - Makola, Raymond Tshepiso (My University, 2015)
Lithium is an FDA-approved psychiatric drug that has been used for more than half a century as a preferred, gold standard treatment for bipolar disorders (Cade, 1949; Freland and Beaulieu, 2012). Numerous studies reported that lithium can play a key role in regulation of inflammation and oxidative stress beyond bipolar disorders since it’s known to target GSK3-β and NF-κB key inflammation molecules (Yestevelasco et al., 2008; Zhang et al., 2008). The choice of this drug was derived from its easy accessibility, less cost, minor side effects and efficacy as opposed to other anti-depressant drugs used currently. This study is based on a body of experimental evidence that has outlined the link between uncontrolled inflammation and some chronic ailments. Thus, this study was aimed at investigating the molecular mode of action of lithium chloride on amelioration of oxidative stress and inflammation in activated Raw 264.7 since, preliminary results of this work suggested the anti-inflammatory properties of lithium. Lithium chloride (LiCl) is not cytotoxic to Raw 264.7 and NIH 3T3 cell lines up to 20 mM and no change in cell proliferation, viability, growth, and cell adhesion were observed as demonstrated using xCELLigence Real Time Cell Analyser (RTCA) and MTT assays. In addition, this drug was shown to be unable to induce programmed cell death in Raw 264.7 and NIH 3T3 cell after 10 mM LiCl treatment as demonstrated using Annexin-V/ PI apoptosis detection assay. Using the Griess and DAF2-DA assays pre-treatment with low doses of lithium (LiCl) was shown to reduce Nitric Oxide production in LPS-induced macrophages. A reduced internal H2DCF-DA fluorescence intensity is indicative of reduced ROS production, observed in lithium-treated Raw 264.7 macrophages stimulated with LPS, FMLP and PMA. Real Time PCR analysis revealed that lithium modulates expression of inflammation inhibitory genes such as IκB-α, TRAF3, Tollip and NF-κB1/p50. This inhibitors are known to play a vital role up stream (Tollip and TRAF3) and downstream (IκB-α and NF-κB1/p50) of NF-κB inflammation signalling pathway. Thus, these molecules are thought to be anti-inflammatory molecular targets of lithium. Moreover, immunocytochemistry suggest that lithium blocks nuclear translocation of NF-κB. This study associates lithium to reduced oxidative stress in LPS, FMLP and PMA-activated Raw 264.7 macrophages in a non-neuronal setting and further suggests lithium as a potential candidate for regulation of oxidative stress conditions beyond bipolar disorders.
Theses (MSc. (Biochemistry)) -- University of Limpopo, 2015
Keywords: Lithium; Inflamation; Oxidative stress; Psychiatric drugs; Oxidation; Inflamation